DESIGN AND IMPLEMENTATION OF HARDWARE INSTRUMENTOFATHLETâSSPEEDMEASUREMENTDEVICE - Fuad Aziz, Tri
Indonesia is a country in the world that has the fourth largest population in the world. However, in recent years, Indonesia has experienced a drastic decline in the field of sports achievements in the world. One reason is the lack of maximum development of the athlete's potential at this time. The potential of an athlete can be identified by conducting a speed and acceleration test through a sprint test at any given distance. At present data retrieval is still done manually using a stopwatch, resulting in uncertainty of varying data retrieval. In the previous year, there has been a prototype development related to the runner time data acquisition system, but there are still a number of things that can be developed further, such as the problem of ballooning, power consumption, data storage, and data transmission. In this research, the design and implementation of hardware for the prototype of speed, acceleration, and endurance speed of an athlete is carried out, which is in the form of a timing gates system. The instrument is able to retrieve athlete speed component data every 10m in a 60m sprint. There are two main sub-systems in taking data on athlete running speed, namely the start sensor sub-system and the gate sensor sub-system. The start sensor sub-system is used as a reference for time synchronization, time calculation, receive of time data from each gate and sending it to the main monitor sub-system. The gate sensor sub-system is used to calculate the time when the athlete passes the distance where the gate sensor sub-system is placed. The hardware in the timing gates system is designed using components: ESP32 microcontroller, green laser pointer 303, OPL5XX laser sensor, buzzer, RGB LED, Sony VTC6 18650 battery, Omnidirectional antenna TL-ANT2405CL, Uneed CompactBox 10000 mAh powerbank. With the time synchronization algorithm and the communication protocol used can minimize the latency that occurs so that what is obtained is a system capable of measuring components of athlete running speed to a distance of 60m with measurements every 10m. Detection of athletes by the system can be done in the range of 0.1 ~ 2m in the direction of the transmitter to the receiver. With the development of an instrument for measuring the components of athletes at an affordable price, it is hoped that the trainer can immediately identify the potential of athletes throughout Indonesia so that in the future they can arrange appropriate training programs.